Semiotic Meaning and Moral Value of ‘‘Mind Over Matters’’ Song By Young The Giant - Marlin Harianja (Journal Corner of Education, Linguistics, and Literature, 2023)
Songs are frequently sung or listened to without knowing the meaning of the lyrics. The song “Mind Over Matter” by Young the Giant is one of the American indie rock songs that has meaning within its lyrics. The purpose of this research is to discover the semiotic meaning and moral values found in the lyrics of the song “Mind Over Matter” by Young The Giant. The method used in this research is a descriptive qualitative method, with the semiotic approach of Ferdinand De Saussure to find the semiotic meaning and moral values present in the lyrics of the song “Mind Over Matter” by Young The Giant. The song “Mind Over Matter” has a meaning that refers to struggle, determination, and spirit in facing life’s challenges. This song depicts someone who is ready to overcome obstacles and uncertainties with the power of the mind and determination. The lyrics in this song can be interpreted as a message not to give up and keep moving forward despite obstacles or uncertainties. This song stimulates thoughts about the importance of maintaining enthusiasm and belief in facing change and difficult situations in life.